REGULATION OF PPARγ FUNCTION BY TNF-α - Ye, Jianping (2008)
The nuclear receptor PPARγ is a lipid sensor that regulates lipid metabolism through gene transcription. Inhibition of PPARγ activity by TNF-α is involved in pathogenesis of insulin resistance, atherosclerosis, inflammation, and cancer cachexia. PPARγ activity is regulated by TNF-α at pre-translational and post-translational levels. Activation of serine kinases including IKK, ERK, JNK and p38 may be involved in the TNF-regulation of PPARγ. Of the four kinases, IKK is a dominant signaling molecule in the TNF-regulation of PPARγ. IKK acts through at least two mechanisms: inhibition of PPARγ expression and activation of PPARγ corepressor. In this review article, literature is reviewed with a focus on the mechanisms of PPARγ inhibition by TNF-α.